Oaks recruitment years and mean tree ring widths - Bobiec, Andrzej (Andrzej Bobiec, 2018)
Recruitment Stand symbols: BNP - Białowieża National Park; Brsk - Białowieża Forest, Browsk district - marginal wood facing floodplain grassland; PL - Carpathian foothills in SE Poland (PLH180012); UA - Prykarpattya, near Rozhniativ, W Ukraine; RO - eastern Transylvania (central Romania, Harghitta region) Recruitment year: callendar year, in whic an oak had gained the recruitment level of 1.3 m RingWidth Stand symbol: see above the explanation Average RingWidth: mean ring width during the first 50 years of growth since the 1.3-m year - for younger oaks at least 30 years.
Keywords: 1.3-m year; Quercus robur and Q. petraea